Factors contributing to acute accidental hypothermia (literature review) - V.V. Yekhalov; O.V. Kravets; D.A. Krishtafor (Медицина неотложных состояний, 2022)
Risk factors for hypothermia include conditions that reduce thermogenesis, disrupt thermoregulation, and increase heat loss. The main groups of risk factors for hypothermia are: low ambient temperature; periodically repeated exposition to cold; reduction of heat production; violation of thermoregulation in severe injuries and diseases; increased heat loss due to anthropological features (age, race, sex, constitution), pathological conditions (skin diseases, vasodilation, motion sickness and other somatic and neurological diseases) or environmental conditions (high thermal conductivity, humidity, wind speed). This literature review of possible causes and factors contributing to general hypothermia may be useful when social and specialized service employees plan measures to prevent accidental hypothermia in workers in various sectors of the economy, military and vulnerable groups, as well as during retrospective analysis of the causes of cold injuries by emergency services, first contact practitioners, combustiologists, and intensive care unit staff.